Reproductive Responses to Wounding and Heat Stress in Gametophytic Thalli of the Red Alga Pyropia yezoensis - Suda, Masahiro; Mikami, Koji (Frontiers in Marine Science, 2020)
The timing of the transition from growth to reproduction is essential for the regulation of the seaweed life cycle. Variable environmental conditions can stress seaweeds and promote trade-offs between their growth and reproduction. Here, we demonstrate that reproductive responses can be induced by environmental stresses in the gametophytic thalli of the marine red alga Pyropia yezoensis. Excision of explants accelerated release of asexual monospores and sexual carpospores. The algal sensitivity to wounding was enhanced by a 3-day dark treatment prior to the excision of the explants. By contrast, heat stress at 25°C stimulated the production of a callus, a three-dimensional aggregation of randomly divided cells with multiple cell layers. This callus produced new gametophytic thalli with a normal shape; therefore, callus formation is thought to be one of the asexual reproductive strategies used by the alga to increase the number of thalli under heat stress conditions. Our results demonstrate that wounding and heat stress can reset the timing of reproduction and that gametophytic thalli therefore use a variety of distinct reproductive strategies under different stress conditions. These findings provide insights into the induction of reproduction by environmental stresses as a life cycle trade-off in seaweeds.